Answer:
a - b2
Step-by-step explanation:
STEP 1
:
Trying to factor as a Difference of Squares:
1.1 Factoring: a-b2
Theory : A difference of two perfect squares, A2 - B2 can be factored into (A+B) • (A-B)
Proof : (A+B) • (A-B) =
A2 - AB + BA - B2 =
A2 - AB + AB - B2 =
A2 - B2
Note : AB = BA is the commutative property of multiplication.
Note : - AB + AB equals zero and is therefore eliminated from the expression.
Check : a1 is not a square !!
Ruling : Binomial can not be factored as the difference of two perfect squares
Final result :
a - b2
<u><em>HOPE THIS HELPS!</em></u>
<u><em>PLEASE MARK BRAINLIEST! :)</em></u>
Answer:
52 R17
Step-by-step explanation:
52 * 36 = 1872
1889 - 1872 = 17
--> 52 R17
Answer:
The answer is B. f(x) = (x − 1)(x − 2)(x + 1)(x + 2)
Step-by-step explanation:
It would be 12
3*8=24 then divide that by 2 which is 12
Answer:
We are learning this in 7th grade lol how did you get 7th grade math to 6th grade math